Decomposition of sugarcane by Irichoderma. - Bangilan, Ma. Irish
Sugarcane bagasse, an end-product after extraction of the juice of the sugarcane, was composted with the aid of Trichoderma, a compost fungus activator which shortens the decomposition process of farm wastes. Decomposition process was observed through the changes in temperature and substrate consistency. An average of 94 days was noted for a coplete decomposition of 900 kg bagasse. Analysis of bagasse compost gave 0.78 nitrogen, 4.94 phosphorus, in the form of P2O2 and 1.55 potassium, in the form of K2O. It showed that composted bagasse is a good source of phosphorus but poor in nitrogen and potassium. The compost, nevertheless can also be a good soil conditioner.